Optimal operation method of integrated energy system considering thermal inertia. Issue 1 (1st February 2022) - Wang, Yongli; Liu, Zhen; Cai, Chengcong; Shen, Hekun; Chen, Xin; Yang, Yang
Abstract: This paper proposes a comprehensive energy system operation optimization method considering the thermal inertia of the heating system. Firstly, based on the energy network of the integrated energy system, establish the thermal inertia and heat storage model of the heating pipeline; secondly, the goal is to minimize the total operating cost of the electricity-heat-gas integrated energy system. Considering constraints such as power balance and safe operation of equipment, an integrated energy system operation optimization model based on thermal inertia is established; the results show that the model can better balance scheduling cost and reliability.